The 1947 Partition of India and Pakistan: Migration, Material Landscapes, and the Making of Nations - Riggs, Erin; Jat, Zahida Rehman (Journal of Contemporary Archaeology, 2017)
The nation state, as a concept, relies on an assumption of boundedness—on the idea that governable units are culturally unified and locationally discrete. Displacement often works to make this boundedness a material reality. Demographics are reshuffled in accordance with essentialist understandings of cultural origins. Yet, displacement also exposes the impossibility of a national sovereignty based neatly on historic spatiality. Even if people are ‘going home’ to what is seen to be an ancestral homeland, they are leaving familiar landscapes shaped by their own personal pasts. In this paper, we discuss the 1947 Partition of India and Pakistan as an example. We describe the yet contended uses and meanings of built landscapes associated with out-migrating Partition refugees on both sides of the border. Through this example, we assert that displacement is not a singular moment, but a long, drawn out negotiation of access and national belonging. Thus, archaeologies of forced and undocumented migration must not begin and end in discussion of hardship-filled border crossings and momentary homelessness. We must also consider the anxiety of post-journey existence within material landscapes that evidence the recent and long-standing occupations of others.